Natural Variation in Flower Color and Scent in Populations of Eruca sativa (Brassicaceae) Affects Pollination Behavior of Honey Bees. Issue 3 (14th May 2019) - Barazani, Oz; Erez, Tal; Ogran, Ariel; Hanin, Nir; Barzilai, Michal; Dag, Arnon; Shafir, Sharoni
Abstract: Plants of Eruca sativa Mill. (Brassicaceae) from desert and Mediterranean populations in Israel differ in flower color and size. In the desert habitat, the population has higher abundance of flowers with cream color and longer petals, whereas in the Mediterranean habitat, the population has higher abundance of flowers with yellow and shorter petals. Choice experiments with honey bee foragers ( Apis mellifera Linn., Apidae, Hymenoptera), the main pollinator in the natural habitat in Israel, confirmed that they are more attracted to the yellow flower morph than to the cream one. A proboscis extension response test indicated that honey bees are able to discriminate between flower scents of the desert and Mediterranean populations. Considering the advantage of plants of the yellow morph in attracting pollinators, we further tested in a common garden experiment whether these possess higher fitness than plants of the desert population. Indeed, a significant association was found between flower color and fruit set, and seed mass. In general, our results provide evidence for ecotypic differentiation between populations imposed by pollinators. The advantage of the yellow color morph in attracting pollinators may explain its dominance among plants of the Mediterranean population. We discuss why the cream color morph may be dominant in the desert habitat, considering the possibility of different pollinators, tradeoffs between traits, or pleiotropy.